Degradation Behaviour Of Treated Betelnut Fibres Reinforced Polyester Composites For Tribological Applications - Nirmal, Umar; Megat Ahmad, Megat Muhammad Hamdan; Yaakob, Mohd Yuhazri; Amir Mohamed, Kamarul (Inderscience Enterprises Ltd., 2018)
The current research aims to study the tribological performance of treated betelnut fibre reinforced polyester (T-BFRP) composite aged in different lubricants with different kinematic viscosity. The test was conducted using a pin on disc (POD) wear test rig at different applied normal loads (5-30 N) at different sliding distances (0-6.72 km) subjected to a smooth stainless steel (AISI-304, 60 HB) counterface at 2.83 m/s of sliding velocity. Results revealed that the specific wear rate (Ws) of T-BFRP composite reduced at higher applied loads, i.e., the reduction in Ws was 90% for AP and 86.3% for P test samples as compared to neat polyester (NP) test samples at 20 N of applied load. This was namely due to the lowest absorption rate incurred by the betelnut fibres when they were aged in their respective aging solutions, i.e., highest kinematic viscosity resulting in lowest absorption rate by the fibres. In other words, at high kinematic viscosities, T-BFRP composite experienced low values in Ws (i.e., low absorption rate by the fibres, lower material removal process due to high fibre surface wettability).